Physical properties of earthworm casts and surface soil as influenced by management - Lal, R.; Akinremi, O.O. (1983)
We compared physical properties of worm casts with the properties of the surface 0 to 5 and 5 to 10 centimeters of soil under different management systems for an Alfisol in southwestern Nigeria. Soil management treatments consisted of comparison of notillage with conventional plowing and harrowing, surface application of residue mulch with no mulch, and application of recommended rate of chemical fertilizer with no fertilizer application. Physical properties of casts were significantly different from those of the soil, and there were also noticeable effects of tillage methods and fertilizer-mulch treatment combinations. Soil and casts from no-till treatments had more favorable physical properties than those from conventionally plowed plots. These differences were significant in terms of the mean weight diameter, moisture retention characteristics, and pore size distribution. The rate of cast production was greater in no-till than in plowed and in mulched than in unmulched treatments.